A Longitudinal Examination of Associations between Age and Chemotherapy-Induced Peripheral Neuropathy in Patients with Gynecologic Cancer - Bulls, Hailey W. (Gynecol Oncol, 2018)
OBJECTIVE: Increasing age has been associated with higher risk of chemotherapy-related toxicities, often resulting in treatment disruptions or discontinuations. Age has also been evaluated as a potential risk factor for chemotherapy-induced peripheral neuropathy (CIPN), but current understanding of recovery from CIPN in older adults after treatment is limited. The goal of the current study was to: 1) evaluate longitudinal change in patient-reported CIPN symptoms from the start of chemotherapy to one year post-chemotherapy; and 2) examine treatment modifications in older (≥65 years) and younger patients (<65 years). METHODS: As part of a larger ongoing study, gynecologic cancer patients (n= 90) treated with cytoxic chemotherapy reported their CIPN symptoms via the EORTC-CIPN20 three times during active treatment and at 6 and 12 months post-treatment. Medical record reviews were conducted to abstract clinical information during active treatment. RESULTS: Piecewise mixed models revealed that older and younger patients reported similar increases in CIPN during the active treatment phase. However, older patients did not recover from CIPN after treatment completion, whereas younger patients exhibited significant declines in CIPN symptoms post-treatment. No age differences were observed in the presence of provider-recorded sensory neuropathy and pain; neuropathy-related treatment delays, changes in chemotherapy dose, regimen, or discontinuations; or falls (all p-values>0.05). CONCLUSIONS: Results from the current study indicate that older adults are at higher risk for chronic CIPN. Older survivors may require additional education and treatment for chronic CIPN symptoms. Additional studies are needed to explore novel interventions to manage chronic CIPN in older cancer survivors.